Antimicrobial activity of herbal extracts: Water borne Pathogenic bacteria - Wagh, Reshma; Patil, Nilatai; Pathade, Girish (Journal of Neonatal Surgery, 2025)
This study investigated the antimicrobial activity of various herbal extract Against common Waterborne pathogenic Bacteria, including & E. coli, Salmonella paratyphi, Micrococcus luteus, Pseudomonas aeruginosa, Micrococcus roseus. Herbal extract from plant Such as Tulsi and Piber Bettel were evaluated by using Agar well diffusion Method. Result demonstrated Significant Antibacterial activity and When Tulsi and Piper Bettel the strongest effects. The findings Suggest that these herbal remedies could serve as alternative treatment for Managing Waterborne infections pathogen. Highlighting their potential as natural antimicrobial agents in public health application